Host plant richness and environment in tropical forest transformation systems shape arbuscular mycorrhizal fungal richness - Edy, Nur; Barus, Henry Novero; Finkeldey, Reiner; Polle, Andrea (Frontiers in Plant Science, 2022)
Transformation of tropical lowland rain forests into rubber and oil palm plantations is the cause of massive loss of vegetation diversity. The consequences for associated mycorrhizal fungi are not fully understood. We hypothesized that forest conversion leads to loss of host-specific and resilience of generalist arbuscular mycorrhizal fungi (AMF). Plant identities and AMF species were determined by molecular barcoding of 112 roots collected in three land-use systems (rain forest, rubber and oil palm plantation) in two landscapes on Sumatra (Indonesia), a world hotspot of forest transformation. The collected roots were from 43 forest plant species, in addition to rubber and oil palm. We detected 28 AMF species of which about 75% were forest-specific, 25% shared among the land use systems and one species was only present in plantation roots. Host specificity of AMF was not detected. Oil palm and rubber roots exhibited a strong reduction in AMF richness compared with roots from rainforests and were differentiated by soil resources. On basis of an individual root, oil palm has a lower AMF species richness than forest or rubber roots. Our results demonstrate that tropical AMF communities are shaped by two mechanisms: (i) root habitat diversity as the result of plant diversity and (ii) habitat properties as the result of plant traits or environmental cues. Collectively, deterioration of habitat diversity and properties exacerbates impoverishment of AMF assemblages.